DIFFERENCES OF GROUNDSTROKE TRAINING METHOD AND HAND EYE COORDINATION ON RALLY 3 MINUTES CAPABILITY IN JUNIO TECAD PEKALONGAN DISTRICT - Dharma, Martha Atika Ayudi; Mukaromah, Siti Baitul; Hidayah, Taufiq (Journal of Physical Education and Sports, 2020)
The research objectives are: Knowing the difference in groundstroke training methods and analyzing the interaction between the Exercise method and Eye-Hand coordination on the ability of a 3-minute rally in the TECAD junior tennis player (Tennis academy Andy) in Pekalongan Regency. Quantitative research design with a 2 x 2 factorial design. The population in this study was TECAD junior tennis player in Pekalongan Regency with 30 players taking samples with purpose sampling of 24 players. The initial data collection uses a hand-eye coordination test after which it is divided into an experimental group and a control group to obtain the results of the exercise method using a paired rally ability test. The analysis technique uses the Kolmogorof Smirnov analysis technique at a significant level of 5% (? = 0.05). The results are shown in the tests of Between-Subjects Effects table showing Sig. = 0.047 for Method variables, significance level ? = 5% = 0.05, Sig value <? or 0.047 <0.05, the conclusion that there are differences in the ability to rally 3 minutes with the groundstroke training method on the TECAD junior tennis player in Pekalongan Regency, Sig. The result for the Coordination variable is Sig. = 0.009, using a significance level of ? = 5% = 0.05, Sig value <? or 0.009 <0.05, the conclusion that there is a difference in the ability of a 3 minute rally with hand-eye coordination on TECAD junior tennis player in Pekalongan Regency, Sig. The interaction between the groundstroke method and hand eye coordination is Sig. = 0.03, significance level ? = 5% = 0.05, Sig value <? or 0.030 <0.05, a conclusion is drawn that there is an interaction between the groundstroke training method and coordination an eye on the ability to rally 3 minutes at the TECAD junior tennis player in Pekalongan Regency. The amount of influence exerted from the interaction between the groundstroke method and hand eye coordination is 40.2%.